Effectiveness of agricultural land use in the lower Danube Euroregion - N. Myshkovetz; D. M. Parmacli (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2010)
The article conducts a comparative analysis of land productivity by major agricultural crop types of the bordering territories in the Lower Danube Euroregion which comprise 196.3 thousand hectares of Romania, 105.1 thousand hectares of Ukraine, 142.2 thousandhectares of Moldova on average within the years of 2004-2007. It computes the level of use of land fertility potential by major types of crops, based on which the average index of land productivity use in the territories of the Lower Danube Euroregion (the Tulcea district of Romania, four districts of Ukraine, and five districts of Moldova) is designed. Keywords: effectiveness of land use, land fertility potential, land productivity, level of use of land fertility potential, average index of land productivity use.